2016
DOI: 10.1097/brs.0000000000001348
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization in Secondary Somatosensory Cortex in Chronic Low Back Pain Patients

Abstract: STUDY DESIGN: A cross-sectional comparative study between chronic low back pain (CLBP) patients and healthy control subjects. OBJECTIVE: The aim of this study was to investigate reorganization in the sensory cortex by comparing cortical activity due to mechanosensory stimulation of the lumbar spine in CLBP patients versus a control group by using functional magnetic resonance imaging (fMRI). SUMMARY OF BACKGROUND DATA: LBP is now the number 1 condition across the world in terms of years living with a disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…In particular, sensory representations and somatosensations were often used in literature as a surrogate for perceptual representations and somatoperception, mainly to describe their associated dysfunctions. Readers are invited to see Flor et al (1997), Flor (2003), and Hotz-Boendermaker et al (2016) for maladaptive reorganizations of somatosensory representations, and Tsay et al (2015) for a comprehensive review on somatosensations. Moreover, we have deliberately avoided the use of the umbrella term "body image" given the controversies and interpretational difficulties with this term (de Vignemont, 2010;Pitron et al, 2018;Gadsby, 2019): it has often been used as a "passepartout" term, lumping together phenomena and psychological capacities quite different from each other, often referred to beliefs and affective attitudes related to the body (Mohr et al, 2010).…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…In particular, sensory representations and somatosensations were often used in literature as a surrogate for perceptual representations and somatoperception, mainly to describe their associated dysfunctions. Readers are invited to see Flor et al (1997), Flor (2003), and Hotz-Boendermaker et al (2016) for maladaptive reorganizations of somatosensory representations, and Tsay et al (2015) for a comprehensive review on somatosensations. Moreover, we have deliberately avoided the use of the umbrella term "body image" given the controversies and interpretational difficulties with this term (de Vignemont, 2010;Pitron et al, 2018;Gadsby, 2019): it has often been used as a "passepartout" term, lumping together phenomena and psychological capacities quite different from each other, often referred to beliefs and affective attitudes related to the body (Mohr et al, 2010).…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Early work by Flor et al [ 6 ] using brain imaging identified somatosensory disorganization in patients with chronic low back pain (CLBP). More recent imaging studies in people with CLBP have shown structural and functional alterations in cortical and subcortical areas, associated with the processing of sensory information [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For low back pain (LBP) in general there has been recent interest in the role that altered body-image that is, the way the body feels to the individual [14], might play in the pain experience [14][15][16]. There is evidence of reorganisation [17][18][19][20][21][22] as well as morphological [23][24][25][26][27][28][29][30] and biochemical changes [31,32] in areas of the brain thought to subserve body-image. Several studies have reported that people with LBP perceive the back as fragile and vulnerable [33][34][35], feel a sense of alienation and rejection of the back [36][37][38], represent the back differently when asked to draw how the back feels to them [39,40] and endorse questionnaire items associated with altered perceptual awareness of the back [16,41,42].…”
Section: Introductionmentioning
confidence: 99%